Modification of social determinants of health by critical illness and consequences of that modification for recovery: an international qualitative study. Issue 9 (27th September 2022) - McPeake, Joanne; Boehm, Leanne; Hibbert, Elizabeth; Hauschildt, Katrina; Bakhru, Rita; Bastin, Anthony; Butcher, Brad; Eaton, Tammy; Harris, Wendy; Hope, Aluko; Jackson, James; Johnson, Annie; et al.
Abstract : Objectives: Social determinants of health (SDoH) contribute to health outcomes. We identified SDoH that were modified by critical illness, and the effect of such modifications on recovery from critical illness. Design: In-depth semistructured interviews following hospital discharge. Interview transcripts were mapped against a pre-existing social policy framework: money and work; skills and education; housing, transport and neighbourhoods; and family, friends and social connections. Setting: 14 hospital sites in the USA, UK and Australia. Participants: Patients and caregivers, who had been admitted to critical care from three continents. Results: 86 interviews were analysed (66 patients and 20 caregivers). SDoH, both financial and non-financial in nature, could be negatively influenced by exposure to critical illness, with a direct impact on health-related outcomes at an individual level. Financial modifications included changes to employment status due to critical illness-related disability, alongside changes to income and insurance status. Negative health impacts included the inability to access essential healthcare and an increase in mental health problems. Conclusions: Critical illness appears to modify SDoH for survivors and their family members, potentially impacting recovery and health. Our findings suggest that increased attention to issues such as one's social network, economic security and access to healthcare is required following discharge from critical care.